Autoimmune Thyroid Disease and Keratoconus: Is There an Association? - Hussam H. Alhawari; Yousef S. Khader; Hussein H. Alhawari; Amal F. Alomari; Hiba N. Abbasi; Muhannd S. El-Faouri; Muawyah D. Al Bdour (International Journal of Endocrinology)
Purpose. The association between autoimmune diseases and keratoconus (KC) has been proposed based on previous retrospective studies and case reports. The aim of our study is to investigate whether KC is associated with autoimmune thyroid disease. Methods. A comparative study was conducted on 131 adult subjects from September 2015 to May 2017 at Jordan University Hospital, Amman, Jordan. Subjects were classified into 2 groups: subjects with autoimmune thyroid disease, including Graves’ disease and Hashimoto’s thyroiditis (n=68), and a healthy group for comparison (n=63). Subjects with any other conditions known to be associated with KC were excluded. The diagnosis of KC was based on clinical and corneal topographic findings utilizing the Oculus-Pentacam machine. In addition, TSH and total T4 levels as well as thyroid peroxidase antibodies were measured in all study participants. Antithyroglobulin antibodies, thyroid stimulating immunoglobulin, thyroid ultrasound, and thyroid uptake and scan were also selectively performed in some participants. Results. This study included a total of 131 participants (101 females and 30 males), including patients and controls. In the multivariate analysis, autoimmune disease was not significantly associated with keratoconus (OR = 1.1; 95% confidence interval: 0.3, 3.8; p value = 0.353) after adjusting for age and gender. Conclusion. This study did not show a statistically significant association between autoimmune thyroid disease and KC.